2015
DOI: 10.1002/ajh.23966
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of therapy‐related myeloid neoplasms: Report from the Italian network on secondary leukemias

Abstract: Therapy-related myeloid neoplasms (t-MN) are a complication of cytotoxic treatment for primary tumors and autoimmune diseases. We report data on 277 t-MN patients, recruited between 1999 and 2013 by the Italian Network on Secondary Leukemias (104 retrospectively and 173 prospectively registered). Median age at t-MN diagnosis was 64 years (range, 21-87). Most frequent primary malignancies (PMs) were lymphoproliferative diseases and breast cancer. One hundred and thirty-three patients had received chemotherapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 28 publications
3
88
1
1
Order By: Relevance
“…[257][258][259][260][261] Therapy may be compromised by a higher treatment-related morbidity and mortality. 259 There is still little prospective treatment data because these patients have often been excluded from frontline clinical trials.…”
Section: Treatment Of T-amlmentioning
confidence: 99%
“…[257][258][259][260][261] Therapy may be compromised by a higher treatment-related morbidity and mortality. 259 There is still little prospective treatment data because these patients have often been excluded from frontline clinical trials.…”
Section: Treatment Of T-amlmentioning
confidence: 99%
“…Also, in this study, neither age nor donor type was associated with worse outcomes [104]. Retrospective data from Fianchi et al showed that patients with t-MN who received HCT have better OS than those who did not (58.8 months for allogeneic SCT vs. 12.1 months, P b0.0001) [75]. Given the retrospective nature of the study, this advantage could be secondary to selection bias.…”
Section: Management Strategies For T-mdsmentioning
confidence: 79%
“…As expected, the IPSS-R risk distribution is in t-MDS/oligoblastic AML is skewed toward higher risk groups (high and very high groups) compared to their de novo counterparts (59.3% vs 23.1%) [16]. Fianchi et al identified age, degree of anemia, and karyotype as important predictors of survival and a simplified prognostic score can be formulated based on these 3 variables [75].…”
Section: Natural History Of T-mds and Prognostic And Risk Stratificatmentioning
confidence: 94%
See 2 more Smart Citations